Multiple sclerosis-related fatigue lacks a unified definition: A narrative review - Iman Adibi; Mehdi Sanayei; Farinaz Tabibian; Neda Ramezani; Ahmad Pourmohammadi; Kiarash Azimzadeh (Journal of Research in Medical Sciences, 2022)
Fatigue is the most common symptom in multiple sclerosis (MS). Although MS-related fatigue (MS-F) strongly affects quality of life and social performance of patients, there is currently a lack of knowledge about its pathophysiology, which in turns leads to poor objective diagnosis and management. Recent studies have attempted to explain potential etiologies as well as treatments for MS-F. However, it seems that without a consensus on its nature, these data could not provide a route to a successful approach. In this Article, we review definitions, epidemiology, risk factors and correlated comorbidities, pathophysiology, assessment methods, neuroimaging findings, and pharmacological and nonpharmacological treatments of MS-F. Further studies are warranted to define fatigue in MS patients more accurately, which could result in precise diagnosis and management.